SOUND THERAPY AND ITS INFLUENCE UPON THE HUMAN BODY - GUŢANU, Stela (Studia Universitatis Babes-Bolyai Musica, 2015)
Various musicological studies highlight the construction of the musical elements and their influence upon people. Today it is unanimously accepted the idea that sound is a part of life and it is an unseen, universal, vibrational force, which can produce essential changes in the human life, spirit and mind. The influence that sounds exerts upon the human body causes significant changes in the sense of healing the human body, re-establishing its balance of vital energies and good health. Sound therapy (or sound healing) is a therapy through sound, being one of the branches of vibrational medicine.